Amicus Curiae dalam Sistem Peradilan Pidana: Perspektif KUHP Nasional dan Perbandingan - Michael Nicola Prayoga (Recht Studiosum Law Review, 2024)
The aim of this article is to examine the function of amicus curiae in the criminal justice system. To analyse this issue, this article uses normative legal research method and two approaches, namely the statutes approach and the comparative approach with the current regulations concerning amicus curiae in The United States of America. This article argues that in the National Criminal Code regime, amicus curiae will increasingly occupy an important and central position. This argument can be seen at least from the formulation of the Article 12 paragraph 2, Article 35, and Article 54. In all of these aspects, the values and sense of justice of the community are important for judges to consider. In this case, amicus curiae plays an important role to show how the community assesses the criminal case being tried. By conducting a comparative study with the regulation of amicus curiae in the United States, this article proposes three aspects to be considered in regulating the implementation of amicus curiae in Indonesia. These three aspects include the affirmation of the position of amicus curiae in Indonesian criminal procedure law, the regulation of the substance of amicus curiae, and the procedure for submitting amicus curiae to the Court.